High concentration of symmetric dimethylarginine is associated with low platelet reactivity and increased bleeding risk in patients with acute coronary syndrome. Issue 213 (May 2022) - Eyileten, Ceren; Gasecka, Aleksandra; Nowak, Anna; Jarosz-Popek, Joanna; Wolska, Marta; Dizdarevic, Al-Medina; Lang, Irene M.; Postula, Marek; Ufnal, Marcin; Siller-Matula, Jolanta M.
Abstract: Background: Dual antiplatelet therapy (DAPT) prevents ischemic events in patients with acute coronary syndrome (ACS), but is associated with increased risk of bleeding events. Symmetric dimethylarginine (SDMA) is one of nitric oxide (NO)-related pathway metabolites and stands as a promising biomarker of early chronic kidney disease (CKD) and cardiovascular diseases (CVDs). Objectives: Our study evaluated the role of SDMA in predicting bleeding events in patients after ACS treated with DAPT. Methods: We compared plasma concentrations of NO-related pathway metabolites in patients with ACS ( n  = 291) and investigated the prognostic value of SDMA as a bleeding predictor during 1-year follow-up. We measured the metabolites concentration using ultra performance liquid chromatography. Platelet reactivity was determined using impedance aggregometry. Results: Patients with the highest quartile (4th) of SDMA concentration had significantly lower platelet aggregation compared to those in the 1st-3rd quartiles of SDMA, based on ADP + PGE1-, AA-, and ADP-induced platelet reactivity tests ( p  = 0.0004, p  = 0.002, p  = 0.014, respectively). Patients with major or minor bleeding events had significantly higher concentrations of SDMA as compared to those without bleeding events or to those with minimal bleeding events ( p  = 0.019, p = 0.019, respectively). Conclusion: Higher SDMA concentration is associated with lower platelet reactivity and is associated with major and minor bleeding events in patients with ACS on DAPT. Therefore, SDMA stands as a potential biomarker for individualization of duration and potency of antiplatelet therapies in the ACS population at high risk of bleeding complications. Highlights: Dual antiplatelet therapy is a risk factor for major and minor bleeding events. Higher SDMA concentration is associated with cardiovascular and chronic kidney disease. We present association between SDMA and platelet reactivity. Higher concentrations of SDMA were in patients with major or minor bleeding events. SDMA is a potential biomarker of bleeding risk in patients on dual antiplatelet therapy.